PEMANFAATAN LIMBAH SABUT KELAPA SAWIT INTUK MENINGKATKAN KEKUATAN TANAH - Hisyam, Endang Setyawati; Yofianti, Desy (SIPIL, 2013)
Soil has a very significant role in construction works, both as the main composition and supporting material. If the construction is build on a soft soil like soft clay, then it will give problem to the construction building. To increase the strength of soil, soil stabilization is done by adding palm pulp fibers into the soil. In this study, the percentages of palm pulp fibers mixed are 1,5%, 2,5%, 3,5%, and 4,5% out of soft clay dry weight. To know the strength of soil, direct shear test and unconfined compressive strength (UCS) test. The mixing of palm pulp fibers affects the value of Soil Shear Strength (s) and Unconfined Compressive Strength (qu). On the level of 4,5%, the Soil Shear Strength (s) and Unconfined Compressive Strength (qu) have the biggest value. The Soil Shear Strength (s) of 129,748 kN/m2 showed a rise of 537,083% in unmixed soil, while the Unconfined Compressive Strength of 34,254 kN/m2 showed a rise of 79,048% in undisturbed soil. Key Words: Clay, Palm pulp fibers, Strength of soil